Key Performance (Benefit) Indicators of Innovative and Investment Activity in Aviation Systems’ Establishment - O. V. Tochilin (Управленческие науки)
The article is devoted to the elements of solving the problems of innovation and investment projecting and assessing the investment projects effectiveness (benefit) in creating high technology products - AS in the aviation industry. In this article the attempt has been done to consider some aspects of the analysis and methods of forming the key performance (benefit) indicators of innovative and investment activity of AS creation and development, which can also help in solving urgent economic problem of elaborating innovation and investment planning methodology (IIPM) in aviation production, which is particularly important for economic, social, scientific and defense value. The various kinds of interactions in the process of fulfillment the programs issues and development plans of AS and other systems are highlighted and offered, such as competitiveness, performing proactive development and financing at the expense of their own resources, evaluation of the integrated utility, control, etc. Some kind of IIPM common performance (benefit) indicators system is proposed which is differentiated according to the type of labor relations, the innovative and investment process stage, the type of control and territorial entities, evaluating the innovation-AS. In addition to methodological approaches, methodical tools of integrated management system (IMS) aircraft company (AC), complex decision-making support “comrade” and IIPM performance (benefit) evaluation - G, S, T (Greybeard, Suvorov, Tochilin) are suggested. The preparation of their program elaboration and practical testing under the conditions of uncertainty and risks have been carried out, which basic method is a complex combined method of decision making preparation and other decisions, which also can help expertise and key performance (benefit) indicators assessment while creating AS.